HORMIGÓN DE BAJA CONDUCTIVIDAD TÉRMICA PARA SU USO EN MAMPUESTOS UTILIZANDO COMO AGREGADOS ESCORIA Y CENIZA DEL VOLCÁN TUNGURAHUA - Valles Andino, Carlos Alberto (2019)
The concretes of low thermal conductivity currently generate a great interest as they help to reduce energy consumption and prevent the burning of fossil fuels to heat homes and residential buildings. By this, the primary objective of this research was to propose a concrete of low thermal conductivity for its use in masonry using as aggregate slag and ash from the Tungurahua volcano. To achieve this objective, tests were carried out on the materials used in the manufacture of the concrete, and through them, the dosages were designed with a pure compressive strength equal to 15 MPa. For each dosage, six test pieces were prepared to be tested at simple compression and six to be examined at thermal conductivity. Thus, it was determined that the use of slag from the Tungurahua volcano reduces the thermal conductivity by 21.10% and the density by 14.22% with respect to the concrete in which heavy aggregate from the Sillahuan mine was used, it was also determined that the use of ash of the Tungurahua volcano increases the strength and density of the use of ash of the Tungurahua volcano increases the strength and density of the concrete with respect to the dosage in which the slag was used. The method of Tungurahua volcano ash does not help to reduce the thermal conductivity of the concrete since when performing an ANOVA variance analysis, the dosages in which ash was used in their respective percentages were found to be significantly equal to the dosage in which slag was used.